The Inflation-Unemployment Trade-off at Low Inflation - Ricci, Luca (IMF Working Papers; Working Paper ;, 2009)
Wage setters take into account the future consequences of their current wage choices in the presence of downward nominal wage rigidities. Several interesting implications arise. First, a closed-form solution for a long-run Phillips curve relates average unemployment to average wage inflation; the curve is virtually vertical for high inflation rates but becomes flatter as inflation declines. Second, macroeconomic volatility shifts the Phillips curve outward, implying that stabilization policies can play an important role in shaping the trade-off. Third, nominal wages tend to be endogenously rigid also upward, at low inflation. Fourth, when inflation decreases, volatility of unemployment increases whereas the volatility of inflation decreases: this implies a long-run trade-off also between the volatility of unemployment and that of wage inflation.